The relationship between tumour necrosis, systemic inflammation, body composition and survival in patients with colon cancer - Ross D. Dolan; Kathryn Pennel; Joshua Thompson; Molly McKenzie; Peter Alexander; Colin Richards; Douglas Black; Tanvir Abbass; Noori Maka; Josh McGovern; Antonia Roseweir; Stephen T. McSorley; et al. (BJC Reports)
Abstract Background In cancer cachexia the relationship between the tumour, its environment and the systemic inflammatory response is not clear. This study aims to examine this relationship in greater detail. Methods Host characteristics included the presence of a Systemic Inflammatory Response (SIR) as measured by Systemic Inflammatory Grade (SIG), sarcopenia (SMI) and myosteatosis (SMD) were measured. Categorical variables were analysed using χ2 test for linear-by-linear association, or χ2 test for 2 by 2 tables. Survival analysis was carried out using univariate and multivariate Cox regression. Results A total of 473 patients were included. Of these, 70.4% were over 65 years of age, 54.8% were male and 49.8% had an ASA grade of 1 or 2. Pathological examination showed that the majority of patients had a T3 (53.7%) or a T4 (34.0%) cancer and 73.0% had evidence of necrosis. A SIG score of 0 or 1 was present in 57.7% of patients. Tumour necrosis was associated with age (p < 0.01), tumour location (p < 0.01), T-stage (p < 0.001), margin involvement (p < 0.05), SIG (p < 0.001), SMI (p < 0.01), SMD (p < 0.05) and 5-year survival (p < 0.001). On multivariate survival analysis in patients with T3 cancers age (HR: 1.45 95% CI 1.13–1.86 p < 0.01), ASA grade (HR: 1.50 95% CI 1.15–1.95 p < 0.01) and SIG (HR: 1.28 95% CI 1.11–1.48 p < 0.001) remained independently associated with survival. Conclusion These results suggest that tumour necrosis and the subsequent SIR could result in profound changes in body composition and survival. Further pre-clinical and clinical work is required to prove causation.